Carvedilol Protects against Doxorubicin-Induced Mitochondrial Cardiomyopathy - Santos, D. L. (2002)
Several cytopathic mechanisms have been suggested to mediate the dose-limiting cumulative and irreversible cardiomyopathy caused by doxorubicin. Recent evidence indicates that oxidative stress and mitochondrial dysfunction are key factors in the pathogenic process. The objective of this investigation was to test the hypothesis that carvedilol, a nonselective [beta]-adrenergic receptor antagonist with potent antioxidant properties, protects against the cardiac and hepatic mitochondrial bioenergetic dysfunction associated with subchronic doxorubicin toxicity. Heart and liver mitochondria were isolated from rats treated for 7 weeks with doxorubicin (2 mg/kg sc/week), carvedilol (1 mg/kg ip/week), or the combination of the two drugs. Heart mitochondria isolated from doxorubicin-treated rats exhibited depressed rates for state 3 respiration (336 ± 26 versus 425 ± 53 natom O/min/mg protein) and a lower respiratory control ratio (RCR) (4.3 ± 0.6 versus 5.8 ± 0.4) compared with cardiac mitochondria isolated from saline-treated rats. Mitochondrial calcium-loading capacity and the activity of NADH-dehydrogenase were also suppressed in cardiac mitochondria from doxorubicin-treated rats. Doxorubicin treatment also caused a decrease in RCR for liver mitochondria (3.9 ± 0.9 versus 5.6 ± 0.7 for control rats) and inhibition of hepatic cytochrome oxidase activity. Coadministration of carvedilol decreased the extent of cellular vacuolization in cardiac myocytes and prevented the inhibitory effect of doxorubicin on mitochondrial respiration in both heart and liver. Carvedilol also prevented the decrease in mitochondrial Ca2+ loading capacity and the inhibition of the respiratory complexes of heart mitochondria caused by doxorubicin. Carvedilol by itself did not affect any of the parameters measured for heart or liver mitochondria. It is concluded that this protection by carvedilol against both the structural and functional cardiac tissue damage may afford significant clinical advantage in minimizing the dose-limiting mitochondrial dysfunction and cardiomyopathy that accompanies long-term doxorubicin therapy in cancer patients.